PROVERBS IN THE PHRASEOLOGICAL DICTIONARY FROM THE WORKS OF CORNELIUS TACITUS - Lehocki-Samardžić, Ana; Zorić, Matija (Proverbium - Yearbook, 2025)
Based on 128 proverbs and sayings attributed to the Roman historian Cornelius Tacitus, as listed in the Latinum in aeternum collection (Marević 2002), this paper explores the connection between the semantic categories of the quoted phrases and their syntactic structures and aims to prove that, despite the possibility of learning Latin sayings formulaically without surface understanding of Latin grammar, their acceptance and reproduction by Croatian speakers are influenced not only by their semantics but also by their deep structural clarity. For this purpose, all the quoted phrases were subjected to an extensive search for their occurrence in the corpus of the Croatian Language Repository (HJR) of the Institute of Croatian Language and Linguistics. The study tested the representation of various Latin surface structures in the HJR corpus, including accusative with infinitive (ACI), nominative with infinitive (NCI), ablative absolute (ABL.APS.), independent finite sentences in the indicative and subjunctive moods, various nominal and verbal collocations or syntagms and the so-called historical infinitives. The paper has established that phrases from Cornelius Tacitus and other Roman and Latin authors with an indisputable depth structure are accepted and present in the HJR corpus, while those with an unclear depth structure, such as the so-called historical infinitives, are completely absent.